Antioxidant and Physicochemical Properties of African Oil Bean (Pentaclethra macrophylla) Seed Oil Blended with Roasted Sesame (Sesamum indicum L.) Seed Oil - Onwuzuruike, U. A.; Uluocha, M. D; Agwo, O. E.; Okwunodulu, I. N.; Ezeanyagu, C. F. (ADAN JOURNAL OF AGRICULTURE, 2026)
This study evaluated the antioxidant and physicochemical properties of African oil bean seed oil (AOBO) blended with roasted sesame seed oil (RSO). Oils were extracted from African oil bean seeds, unroasted sesame seeds, and roasted sesame seeds. AOBO was blended with unroasted and roasted sesame seed oil at two ratios: 90:10 and 85:15, respectively, using soybean oil as the reference. Following extraction, oil yields were calculated (AOBO: 47.95%; Unroasted Sesame: 46.88%; RSO: 53.70%). The unmixed and blended oils were assessed for their physicochemical properties (viscosity, refractive index, specific gravity, melting point, cloud, smoke, flash, and fire points) and antioxidant activity (DPPH, ABTS, and FRAP assays). Physicochemical properties varied, ranging from 36.66–42.06 cP for viscosity, 29.80–31.09°C melting point, 185.49–191.85°C smoke point and 319.05–337.94°C (flash point). Antioxidant activity assays showed values of 3.51–11.03% (FRAP), 54.74–96.28% (DPPH), and 46.27–91.47% (ABTS). The results indicate that blending African oil bean and roasted sesame oils achieved a product with better complementary benefits: enhanced thermal stability from higher smoke (185.49 – 191.85) and flash points (319.05 - 337.94), improved fluidity due to improved viscosity and melting point, and robust antioxidant activity than African oil bean seed oil blended with unroasted sesame seed oil. These findings suggest the potential of the blended oil as a versatile ingredient in culinary and nutraceutical applications. This study contributes to understanding how oil blending can optimize both the functional and health-promoting qualities of vegetable oils, particularly those derived from underutilized food material.